Πειραματική και αριθμητική διερεύνηση της μηχανικής συμπεριφοράς ρωγματωμένων δοκών πετρώματος - Θεοχάρης, Μηνάς (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανικών Μεταλλείων Μεταλλουργών. Τομέας Μεταλλευτικής. Εργαστήριο Τεχνολογίας Διάνοιξης Σηράγγων, 2017)
This thesis studied the mechanical behavior of transverse jointed rock beams, by performing bending tests using an experimental device, which was placed under the bending machine. We have used three different materials, of which the rock beams were comprised. The materials were gypsum, cement and marble (Dionysos and Bolakas marble). Totally we used four gypsum beams, with 60cm lenght each (Each beam consists of 6 cubic pieces – The dimension of each cubic piece is 10cm x 10cm x 10cm), two cement beams,with 60cm length each (Each beam consists of 6 cubic pieces – The dimension of each cubic piece is 10cm x 10cm x 10cm), one Dionysos marble beam, with 60 cm length (The beam consists of 12 cubic pieces – The dimension of each cubic piece is 5cm x 5cm x 5cm) and one Bolakas marble beam, with 60cm length (The beam consists of 12 cubic pieces – The dimension of each cubic piece is 5cm x 5cm x 5cm). Simultaneously with the bending test we used in each beam acoustic emission, for the correlation of the mechanical response of the rock with the events of acoustic emission. For the processing of the data of acoustic emission, we have used the software package Noesis, provided by the Tunnelling Laboratory. We have performed also characterization tests in cylindrical gypsum and cement pieces, and specifically uniaxial compressive tests to measure the uniaxial compressive strength σc of the materials, the elastic modulus E, as well as Brazilian tests, to measure the tensile strength of the materials. Finally, we performed for all the different material beams numerical simulations of the mechanical behavior of the beams using the software package Phase2 version 9.0, by Rocscience. The objectives of this thesis were: • Monitoring each form of failure. • Measurement of the axial force developed in the beams during bending. • Acoustic emission correlation with the mechanical response of rock beams. • Numerical simulation of rock beams.